Environmental assessment of a heating, cooling and electric energy grid from a geothermal source in Southern Italy. (15th November 2022) - Maione, A.; Massarotti, N.; Santagata, R.; Vanoli, L.
Abstract: The development of human societies, of lifestyles and of technologies are responsible for increasing trends of the worldwide energy consumption and of the related greenhouse gas emissions, in addition to a widespread energy inequality. Therefore, novel solutions are much needed to address the global need for energy without further degrading natural and urbanized ecosystems. This work proposes a sustainable medium enthalpy geothermal system in Campania region, Southern Italy, capable of generating electricity and thermal energy with low environmental impacts. The electricity, produced by means of an Organic Rankine Cycle (ORC), is sent to the Italian electricity grid. The thermal energy is used for providing district heating and cooling to office and residential buildings. The designed system is assessed by means of the life cycle assessment method, in order to understand the kind, amount and hot spots of the related environmental burdens. The current heating and cooling configuration in the considered buildings is compared to possible improvement scenarios and to the investigated case study, while the generated electricity is compared to the conventional electricity production from the Italian mix. In both cases, the investigated system shows significant benefits, performing better than common energy systems, with reductions of around 90% in terms of impacts on different environmental compartments. Graphical abstract: Image 1 Highlights: A Geothermal grid for electricity and district heating and cooling is assessed. The environmental impacts are investigated by means of Life Cycle Assessment. The impacts of the grid are compared to current and improved scenarios. The case study presents suitable solutions towards energy transition.